POSITIONAL RESOURCES OF SOUTHERN COASTAL ISLANDS WITH ISSUES OF NATIONAL DEFENCE, SECURITY, AND SOCIO - ECONOMIC DEVELOPMENT - An, Le Duc; Khanh, Uong Dinh; Thanh, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2009)
The positional resources of Việt Nam coastal islands consist of 4 groupes and 16 elements. Among coastal islands of Nam bo, the islands included Phú Quốc, Thổ Chu and Côn Đảo have the most importance on the positional resources. The estimated elements of positional  resources  consist  of:  geographic  position,  frontier-advanced  position,  gateway position from mainland and strategic position for politics and military. The benefits created by the positional  resources  of  coastal  islands,  consist  mainly  of: enlargement  of  the  internal water areas and state sovereignty on sea; strengthening national defence and security; and sea-island socio-economic development.